2016
DOI: 10.1007/s00330-016-4320-8
|View full text |Cite
|
Sign up to set email alerts
|

Contrast volume reduction using third generation dual source computed tomography for the evaluation of patients prior to transcatheter aortic valve implantation

Abstract: • Reduction of contrast agent volume is crucial in patients with chronic renal failure. • Novel third-generation computed tomography helps to reduce contrast agent volume. • Pre-procedural CT allows comprehensive imaging for procedural success before heart valve implantation. • A low-contrast CT protocol is feasible for pre-procedural TAVI planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 30 publications
3
28
1
1
Order By: Relevance
“…A pre-procedural CTA allows for annulus sizing, device selection, evaluation of suitability of the peripheral arteries for access, as well as selection of appropriate fluoroscopic projections and is considered vital for procedural success of TAVR (19). Candidates for TAVR often have co-morbidities such as chronic renal failure that can adversely impact outcomes (20)(21)(22). There has been ongoing debate about the actual incidence, significance and even existence of acute kidney injury following intravenous iodinated contrast media injection during CT (23)(24)(25)(26)(27)).…”
Section: Low Dose Tavr Ctamentioning
confidence: 99%
See 2 more Smart Citations
“…A pre-procedural CTA allows for annulus sizing, device selection, evaluation of suitability of the peripheral arteries for access, as well as selection of appropriate fluoroscopic projections and is considered vital for procedural success of TAVR (19). Candidates for TAVR often have co-morbidities such as chronic renal failure that can adversely impact outcomes (20)(21)(22). There has been ongoing debate about the actual incidence, significance and even existence of acute kidney injury following intravenous iodinated contrast media injection during CT (23)(24)(25)(26)(27)).…”
Section: Low Dose Tavr Ctamentioning
confidence: 99%
“…Bittner et al reported good to excellent image quality with mean attenuation of 285±60 and 289±74 HU at the aortic annulus and iliac bifurcation respectively. The average iodinated contrast material (Iomeron 350) dose used in this study was 38 mL compared to a reference range of 80 and 120 mL for routine dose pre-TAVR CTA (20,29). Scan parameters included tube voltage 100 kV, 350 mAs, 2×192×0.6 mm 3 collimation, 250 ms rotation time and a pitch of 3.2.…”
Section: Low Dose Tavr Ctamentioning
confidence: 99%
See 1 more Smart Citation
“…[20], [21], [22] These studies demonstrate that contrast agent injection can be minimized to 40–60 mL, providing acceptable image quality for the heart and of the entire aorta of TAVI candidates. However, only the minority of centers performing TAVI have the latest dual-source generation scanners available.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast-enhanced CT, new-generation, dual-source CT and dedicated CT protocols offer sufficient imaging data with low dose of contrast media. [12][13][14] We used a second-generation, dual-source CT scanner ( Somatom Definition Flash, Siemens Healthcare, Forchheim, Germany) with low tube current and 100 kV, which were suggested by the automatic exposure control software CareDose 4D (Siemens Healthcare). Magnetic resonance angiography (MRA) has been reported to be equivalent to contrast-enhanced CT for the calculation of aortic annulus 15,16) but inferior for the assessment of aortic valve calcification and access root.…”
Section: Discussionmentioning
confidence: 99%